NUTRITION IN SUBJECTS WITH COMPLETE DENTURES: ENERGY AND MACRONUTRIENT INTAKE - Rouzha Pancheva; Desislava Konstantinov; Mariana Dimova-Gabrovska (Peytchinski Publishing, 2018)
Introduction: There are many factors that have an influence on the nutritional status of older people, but the significance of nutrition for the quality of life is indisputable. Complete tooth loss affects and changes nutritional habits, which poses important questions about the intake of energy and macronutrients in subjects with complete dentures. The aim of this study was to make a comparative analysis of the energy and macronutrient intake in subjects with complete dentures, based on the Bulgarian recommendations for the physiological needs. Materials and methods: An individual questionnaire was used to collect the primary information, covering the following areas: demographic, co-morbid and 3-day dietary intake registered data, as well as a dental examination to confirm the total tooth loss. The investigation was conducted between March and April 2017 in Sofia and Varna. The study included 28 subjects, aged 47 to 89 years. Statistical data processing was performed with the SPSS software for Windows 15.0. Results: The average daily energy intake levels were by about 200 kcal higher than the reference needs for the male subjects with low physical activity, aged over 60 years and close to the recommended for the female subjects. For both sexes, protein intake levels corresponding to the reference, but at the expense of animal proteins (>60%); low carbohydrate intake levels (<40%), but increased intake of added sugars (10-12%); low intake of dietary fibers (<25 grams); high intake of fats, mostly at the expense of saturated fatty acids, were found. Conclusion: Unfavorable tendencies were identified in the nutrition of subjects with total tooth loss, which may further contribute to a worsening of their co-morbid conditions.